2022
DOI: 10.1113/jp283552
|View full text |Cite
|
Sign up to set email alerts
|

The ketogenic diet prevents steatosis and insulin resistance by reducing lipogenesis, diacylglycerol accumulation and protein kinase C activity in male rat liver

Abstract: where she earned a Master's degree conducting research on the molecular mechanisms underlying antibacterial resistance. As a PhD candidate in Dr Ceddia's lab, her current research focuses on understanding the effects of nutritional manipulation on physiological and molecular mechanisms that regulate glucose and fatty acid metabolism in skeletal muscle and liver in both males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
0
33
1
Order By: Relevance
“…Jani et al. (2022) demonstrated that rats fed a KD gained significant weight and fat pad mass, and while not examined in this study, previous work shows that the high saturated fat content of a KD results in increased low density lipoproteins (Crosier & McPherson, 2022). Additionally, the specific KD used by Jani et al.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Jani et al. (2022) demonstrated that rats fed a KD gained significant weight and fat pad mass, and while not examined in this study, previous work shows that the high saturated fat content of a KD results in increased low density lipoproteins (Crosier & McPherson, 2022). Additionally, the specific KD used by Jani et al.…”
Section: Introductionmentioning
confidence: 57%
“…The KD and the SC diet appear to have beneficial effects with respect to liver health, as shown by the novel findings of Jani et al. (2022). This follows previous work on the KD, insulin sensitivity and hepatic steatosis (Luukkonen et al., 2020; Tendler et al., 2007).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations